The Quality of Frozen Semen of Limousin Bull in Various Semen Diluents - A. A. Arif; T. Maulana; E. M. Kaiin; B. Purwantara; R. I. Arifiantini (Tropical Animal Science Journal, 2022)
Diluents are substances added to the semen to increase the semen volume, reduce sperm density, and maintain sperm viability. This study aimed to compare the effects of various semen diluents on the quality of frozen semen of Limousin bull. Three mature Limousin bulls were used as semen sources. The semen was collected using an artificial vagina and then evaluated for its quality. Sperms with motility less than 70% and abnormality greater than 20% were excluded from this study. After semen evaluation, each ejaculate was individually divided into four equal tubes and diluted with skimmed milk-egg yolk (SMEY), Tris–egg yolk (TEY), Tris–egg yolk–skimmed milk (TEYSM), or Andromed®. Diluted semen was loaded into a mini straw and then equilibrated at 5 °C for 4 h. Following equilibration, the straws were frozen. The percentages of sperm motility, viability, intact membrane, and sperm DNA integrity were evaluated after freezing. Furthermore, malondialdehyde (MDA) and aspartate aminotransferase (AST) enzyme concentrations were assessed after thawing. The sperm motility with TEY, TEYSM, and Andromed® did not differ significantly but was higher than with SMEY. Sperm viability, membrane intactness, and sperm DNA integrity did not differ among treatments. By contrast, the MDA levels and concentration of AST in the Andromed® diluent semen showed the lowest values compared with SMEY semen (p<0.05) but did not differ from those of TEY and TEYSM semen. To conclude, TEY, TEYSM, and Andromed® diluents performed equally well, and although they showed better results than SMEY, sperm diluted in SMEY are still suitable for artificial insemination.